1991
DOI: 10.1123/ijsn.1.3.249
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ingesting Polylactate or Glucose Polymer Drinks during Prolonged Exercise

Abstract: Five trained, fasted male cyclists rode a cycle ergometer three times at 50% of,max for 180 min. Using a balanced order, double-blind procedure,subjects were given either a solution containing polylactate (PL: 80% polylactate, 20% sodium lactate, in 7% solution with water), glucose polymer (GP: multidextrin in 7% solution with water), or control (C: water sweetened with aspartame) 5 min before exercise and at 20-min intervals during exercise. Venous blood samples were taken at rest and at 20-min intervals duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 7 publications
1
25
0
5
Order By: Relevance
“…Originally, we wanted to compare a 7 % PL solution to a 7 % GP solution, but we were unable to use PL in concentrations 2.5 % because the supplement, as supplied by the manufacturer and under our experimental conditions, produced severe gastro-intestinal distress within 1-3 hours after the start of a trial. Fahey et al (14) also found that PL had a similar effect on most of their subjects (personal communication). Their test mixture, however, contained 5.6 grams of PL and 1.4 grams of sodium lactate per 100 ml of water.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Originally, we wanted to compare a 7 % PL solution to a 7 % GP solution, but we were unable to use PL in concentrations 2.5 % because the supplement, as supplied by the manufacturer and under our experimental conditions, produced severe gastro-intestinal distress within 1-3 hours after the start of a trial. Fahey et al (14) also found that PL had a similar effect on most of their subjects (personal communication). Their test mixture, however, contained 5.6 grams of PL and 1.4 grams of sodium lactate per 100 ml of water.…”
Section: Resultsmentioning
confidence: 75%
“…It is doubtful that such an effect would prolong aerobic endurance, but it could improve the ability to perform intense, short duration exercise, such as been shown for bicarbonate induced alkalosis (11,16,18,29). Fahey et al (14) found that a 7% PL solution significantly increased blood pH, a finding which suggests that PL may have similar performance effects as bicarbonate. We were unable, however, to corroborate Fahey's finding, as the GP/PL mixture and the GP solution had similar, non-significant effects on blood pH.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Contudo, apenas um estudo apresentou resultados positivos, com uma grande melhora de 25% no desempenho aeróbio (AZEVEDO et al, 2007). No entanto, como há aumento dos níveis de pH (FAHEY et al, 1991;MORRIS, et al, 2011;PAINELLI et al, 2014) e bicarbonato (FAHEY et al, 1991;PAINELLI et al, 2014) (MCNAUGHTON, et al, 1999), pois pode promover um incremento maior no bicarbonato sanguíneo com o maior período de suplementação, mas esse protocolo ainda precisa ser explorado. Os dados estão apresentados como média ± desvio-padrão.…”
Section: Suplementação De Bicarbonatounclassified